Development of portable electrocardiogram (ECG) system - Muhammad Osman Adnan
This main objective in this project is to design and construct a compatible ECG circuit to minimize the size of ECG itself. To construct portable ECG by using any transmission devices, to interface the hardware part and computer software and to display the ECG waves at any output panel.